2017
DOI: 10.1371/journal.pone.0187235
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in non-structural carbohydrates, sucrolytic activity and secondary metabolites in deciduous and perennial Diospyros species sampled in Western Mexico

Abstract: This study was performed to test the working hypothesis that the primary determinants influencing seasonal driven modifications in carbon mobilization and other key biochemical parameters in leaves of poorly known Diospyros digyna (Ddg; semi-domesticated; perennial) and D. rekoi (Dre; undomesticated; deciduous) trees are determined by environmental growing conditions, agronomic management and physiological plasticity. Thus, biochemical changes in leaves of both trees were recorded seasonally during two success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 66 publications
4
28
1
Order By: Relevance
“…This suggested that the significantly lower NSCs accumulation detected in the D. rekoi fruits from 2015 was not due to an impaired and or developmentally regulated capacity to convert starch into reducing sugars, as described in kiwifruits . The previously reported lower nitrogen reserves available to D. rekoi trees at the sampling site also led to discarding the possibility that high nitrogen availability could have negatively affected soluble sugars and starch contents in fruits and other tissues of D. rekoi trees, as shown previously in certain D. kaki varieties . Moreover, they disagreed with a study showing that wild apple fruits, although significantly more acidic than cultivated apples, had average sugar concentrations that were similar to cultivated genotypes .…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…This suggested that the significantly lower NSCs accumulation detected in the D. rekoi fruits from 2015 was not due to an impaired and or developmentally regulated capacity to convert starch into reducing sugars, as described in kiwifruits . The previously reported lower nitrogen reserves available to D. rekoi trees at the sampling site also led to discarding the possibility that high nitrogen availability could have negatively affected soluble sugars and starch contents in fruits and other tissues of D. rekoi trees, as shown previously in certain D. kaki varieties . Moreover, they disagreed with a study showing that wild apple fruits, although significantly more acidic than cultivated apples, had average sugar concentrations that were similar to cultivated genotypes .…”
Section: Discussioncontrasting
confidence: 56%
“…Thus, fewer fruits could be sampled, specifically from one and two tree specimens in the 2015 and 2016 winter seasons respectively. The observed difference most probably reflected the fact that D. rekoi fruits were sampled from trees growing in the wild, whereas domesticated D. digyna trees were raised under more controlled conditions . D. rekoi fruits were much smaller, had a higher seed/edible pulp ratio, and a lower edible portion percentage (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations